A more sustainable energy strategy for India - Montek S. Ahluwalia; Himanshu Gupta; Nicholas H. Stern (Indian Council for Research on International Economic Relations (ICRIER), 2016)
The COP-21 meeting in Paris produced an important result. For the first time all countries developed and developing agreed to take some mitigation action. However even if all countries deliver on what they have promised by 2030 and progress thereafter continues only at the same rate global temperature is likely to be more than 3êC degrees above pre industrial levels by 2100. To get on a 2-degree trajectory will require much more ambitious pledges from all countries and the developed countries have a specially important role to play not only in achieving more ambitious mitigation goals themselves but also in offering financial support for developing countries to do more. Assuming that developed countries show a willingness to do more, it will be necessary for developing countries to consider what more they can do. In the spirit of such an exercise this paper analyses what is possible as a low carbon scenario for India using India Energy Security Scenarios-2047 tool developed by the erstwhile Planning Commission and later refined by its successor NITI Aayog. The calculator allows us to adopt the more ambitious targets deemed feasible and consider the outcomes in terms of reduction in carbon emissions reduction, improvements in air quality, water constraints, and budget implications. The paper elaborates the multiple policy interventions that are needed to achieve these objectives. We find that there is scope for a low carbon growth path which would greatly reduce the level of emissions compared to a business as usual projection for the same growth rate of GDP. This calls for a combination of measures which increase energy efficiency i.e. reduce the emissions intensity of GDP, and shift the composition of energy towards cleaner energy sources. Interestingly we find that although most of the public attention is devoted to green sources of energy, about 86% of the mitigation potential in India comes from interventions focussing on energy efficiency measures, building better cities and encouraging behaviour changes among consumers. The remaining 14% comes from deploying low carbon technologies in the electricity and the fuels sector. The different policy instruments involved in bringing about these changes are indicated. They fall in the domains of different levels of government national, state and local and coordination of all these levels to achieve a common end is a challenge.
Keywords: F10; F13; F50; 330; Climate Change; Global Warming; Intended Nationally Determined Contributions (INDCs); Sustainable Development; Green House Gas (GHG) emissions; Carbon Credits; Energy Security; Air Pollution; Water Crisis